Generation of a homozygous RANGRF knockout hiPSC line by CRISPR/Cas9 system - Meiling Jiang; Chengcheng Tang; Xian Luo; Xiaoqing Zhou; Min Chen; Yue Chi; Liangxue Lai; Qingjian Zou (Stem Cell Research, 2023)
The RAN Guanine Nucleotide Release Factor (RANGRF) gene encodes the protein MOG1, which binds to Nav1.5 and facilitates its transport to the cell membrane. Nav1.5 mutations have been linked to various cardiac arrhythmias and cardiomyopathy. To investigate the role of RANGRF in this process, we utilized the CRISPR/Cas9 gene editing system to generate a homozygous RANGRF knockout hiPSC line. The availability of the cell line will prove to be an invaluable asset in the study of disease mechanisms and the testing of gene therapies for cardiomyopathy.